Social Acceptance of Integrated Photovoltaic Systems in Italian Heritage and Landscape Contexts - Dario Bottino-Leone; Agnieszka Elzbieta Stawinoga; Jennifer Adami; Alexandra Troi; Daniel Herrera-Avellanosa (Buildings)
This study investigates the social acceptance of integrated photovoltaic (IPV) systems in heritage and landscape contexts, focusing on Italian stakeholders in the construction sector. As part of the “BIPV meets History” research project, this study aims to identify barriers, potentials, drivers, and challenges for widespread PV technology adoption, considering heritage conservation, land preservation, energy production, and climate mitigation. A survey exploring opinions on PV technology integration was conducted. The survey was improved and extended to a total of 271 respondents, using the online method of Computer-Aided Web Interviewing (CAWI), to understand how perceptions of integrated photovoltaics have changed after COVID-19 and the European energy crisis, emphasizing aesthetic, environmental, economic, and personal aspects. The results indicate a general awareness of the technologies, with increasing acceptance in protected contexts, for historic buildings (from 51 to 68%) and especially landscapes (from 44 to 71%), driven by energy and environmental benefits. Cultural concerns, particularly the risk of impacting historical and natural identities, emerge as major barriers. Additionally, it is evident that awareness of PV panel recycling methods is still limited.